Maternal characteristics and obstetrical complications impact neonatal outcomes in Indonesia: a prospective study - Trisari Anggondowati; Ayman A. E. El-Mohandes; S. Nurul Qomariyah; Michele Kiely; Judith J. Ryon; Reginald F. Gipson; Benjamin Zinner; Anhari Achadi; Linda L. Wright (BMC, 2017)
Abstract Background We investigated associations between maternal characteristics, access to care, and obstetrical complications including near miss status on admission or during hospitalization on perinatal outcomes among Indonesian singletons. Methods We prospectively collected data on inborn singletons at two hospitals in East Java. Data included socio-demographics, reproductive, obstetric and neonatal variables. Reduced multivariable models were constructed. Outcomes of interest included low and very low birthweight (LBW/VLBW), asphyxia and death. Results Referral from a care facility was associated with a reduced risk of LBW and VLBW [AOR = 0.28, 95% CI = 0.11-0.69, AOR = 0.18, 95% CI = 0.04-0.75, respectively], stillbirth [AOR = 0.41, 95% CI = 0.18-0.95], and neonatal death [AOR = 0.2, 95% CI = 0.05-0.81]. Mothers age <20 years increased the risk of VLBW [AOR = 6.39, 95% CI = 1.82-22.35] and neonatal death [AOR = 4.10, 95% CI = 1.29-13.02]. Malpresentation on admission increased the risk of asphyxia [AOR = 4.65, 95% CI = 2.23-9.70], stillbirth [AOR = 3.96, 95% CI = 1.41-11.15], and perinatal death [AOR = 3.89 95% CI = 1.42-10.64], as did poor prenatal care (PNC) [AOR = 11.67, 95%CI = 2.71-16.62]. Near-miss on admission increased the risk of neonatal [AOR = 11.67, 95% CI = 2.08-65.65] and perinatal death [AOR = 13.08 95% CI = 3.77-45.37]. Conclusions Mothers in labor should be encouraged to seek care early and taught to identify early danger signs. Adequate PNC significantly reduced perinatal deaths. Improved hospital management of malpresentation may significantly reduce perinatal morbidity and mortality. The importance of hospital-based prospective studies helps evaluate specific areas of need in training of obstetrical care providers.